Description of Knowledge, Attitude, and Hygiene Sanitation Behavior among Food Handlers at “PJ” Catering, Surabaya - Fadila Briliyana; Mujayanto Mujayanto; Inne Soesanti; Nuning Marina Pengge (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Hygiene and sanitation are essential to ensuring food safety, particularly in the catering industry. The knowledge, attitudes, and practices (KAP) of food handlers significantly influence the quality and safety of food served. A preliminary study at “PJ” Catering Surabaya found that while food handlers had generally good knowledge, their attitudes and practices remained suboptimal. This gap between knowledge and practice is critical, as it increases the risk of food contamination, threatens consumer health, and can undermine trust in catering services. This study aimed to assess the hygiene and sanitation-related KAP of food handlers during food processing. A descriptive cross-sectional design was used, involving all seven food handlers through total sampling. Knowledge and attitudes were measured using structured questionnaires, and practices were observed directly. Data were analyzed descriptively using frequency distribution. Results showed that 71.4% of respondents had good knowledge and 71.4% had good attitudes. However, practices in ingredient selection, storage, and food serving were only sufficient (42.85–57.15%). These findings emphasize the need for continuous training and regular supervision to improve hygiene and sanitation practices. Strengthening these aspects is essential to ensuring consistent food safety, maintaining service quality, and protecting consumer health in catering operations.